Neonatology : simple & easy - Brucknerová, Ingrid; Lekárska fakulta Univerzity Komenského v Bratislave (Bratislava : Univerzita Komenského v Bratislave, 2021)
The second part of "Neonatology, Simple and Easy", the second edition, which will deal with further characteristic problems of the newborn. This book is intended to give students of medicine a comprehensive view by presenting morphological evidence of cardiac function in normal and pathological conditions, thus combining structure and function of the heart. A further aim is to alert readers to the use of correct medical terminology, which is based on anatomical nomenclature. Examination of the heart, especially in the neonatal period, is the dominant topic of the book, along with a focus on changes that occur physiologically after birth. Only comprehensive theoretical knowledge will help students to master the specific problems of the neonate.
Anglický a latinský register
Bibliogr. odkazy
Keywords: neonatológia; systém kardiovaskulárny; učebnica